Niveles lagrimales y plasmáticos de leptina, endotelina-1 y clusterina, correlación con diagnósticos de retinosis pigmentaria y retinopatía diabética y factores de riesgo (2021)
Retinitis pigmentosa and diabetic retinopathy are neurodegenerative eye diseases. Molecules such as LEP, ET-1, and CLU are described as present in these pathologies, their expression in biological fluids could be considered useful in supporting the diagnosis of the two pathologies.